A Rare Case of Autoimmune Pulmonary Alveolar Proteinosis Developing During the Course of Eosinophilic Granulomatosis With Polyangiitis - Yoichi Dotake; Kentaro Tanaka; Shiro Fujisaki; Kenichi Shimobaba; Hirotoshi Kuroiwa; Midori Satomura; Hiromi Matsuyama; Koichi Takagi; Hideo Mitsuyama; Hiromasa Inoue (Respirology Case Reports)
ABSTRACT Eosinophilic granulomatosis with polyangiitis (EGPA) is an anti‐neutrophil cytoplasmic antibody (ANCA)‐associated vasculitis characterised by asthma, eosinophilia, and systemic inflammation, often involving the lungs. We present the case of a 47‐year‐old woman with EGPA who developed progressive ground‐glass opacities and a crazy‐paving pattern on chest computed tomography (CT). Bronchoalveolar lavage revealed milky fluid, and transbronchial lung biopsy showed periodic acid‐Schiff (PAS)‐positive eosinophilic granular material. Elevated anti‐granulocyte‐macrophage colony‐stimulating factor (GM–CSF) antibodies confirmed a diagnosis of autoimmune pulmonary alveolar proteinosis (aPAP). Corticosteroid tapering initially led to EGPA relapse, which was successfully controlled with mepolizumab, enabling further steroid reduction. Following this, the radiological findings of aPAP showed gradual improvement. In rare cases, it is known that autoimmune diseases such as vasculitis can be complicated by aPAP. This case highlights the importance of individualised immunomodulatory treatment and close imaging follow‐up in patients with overlapping autoimmune conditions.